Indoor relative humidity and air mycobiome in eastern Taiwan residences: associations with Aspergillus and Wallemia - Nicholas T. Minahan; Chi-Hsien Chen; Chih-Cheng Hsu; Yu-Chen Chuang; Xiang-Ting Ma; Yue Leon Guo (Building and Environment, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Biochar reshapes phosphorus distribution in soil aggregates and improves rice phosphorus uptake - Jiajun Wu; Bin Zhou; Zhehao Huang; Zichuan Li; Jingyuan Pan; Kaihao Zhang; Cheng Liu; Yanjun Chai; Yan Li; Muhammad Azeem; Nicholas Clarke; Shengdao Shan (Soil Ecology Letters, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Quantification of per- and polyfluoroalkyl substances (PFASs) in aqueous film-forming foam (AFFF)-impacted water: Comparisons between methodologies and laboratories - Chuhui Zhang; Nicholas Gonda; Ashley N. Kimble; Eric Redman; Cynthia M. Grim; Siwei Gu; Anthony Bednar; Karen Dahl; Chenyi Yuan; Yue Zhi; Hefa Cheng; Christopher P. Higgins (Journal of Hazardous Materials, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Colloidal and interfacial properties of spray dried pulse protein-blueberry polyphenol particles in model dispersion systems - Yufeng Lin; Nicholas Cheng; Yueyue Jiang; Mary H. Grace; Mary Ann Lila; Roberta Targino Hoskin; Haotian Zheng (Food Chemistry, 2024)

Segmentation of beach plastic fragments’ contours based on self-organizing map and multi-shape descriptors: A rapid indication of fragmentation and wearing types - Lei Su; Xinyue Dong; Junjie Peng; Hong Cheng; Nicholas J. Craig; Bo Hu; Juan-Ying Li (Journal of Hazardous Materials, 2024)

Pharmacokinetic Profile of Brepocitinib with Topical Administration in Atopic Dermatitis and Psoriasis Populations: Strategy to Inform Clinical Trial Design in Adult and Pediatric Populations - Farzaneh Maleki; Cheng Chang; Vivek S. Purohit; Timothy Nicholas (Pharmaceutical Research, 2024)
Introduction Topical brepocitinib, a tyrosine kinase (TYK)2/Janus kinase (JAK)1 inhibitor, is in development for psoriasis (PsO) and atopic dermatitis (AD). Quantitative analyses of prior clinical trial data were used to inform future clinical trial designs. Methods Two phase 2b studies in patients with AD and PsO were used to characterize the amount of topical brepocitinib and the resultant systemic trough concentration ( C Trough ) using a linear mixed-effects regression (LMER). This model was used to predict brepocitinib systemic C Trough for higher treated body surface areas (BSAs) in adults and children. Information from non-clinical and clinical trials with oral brepocitinib was leveraged to set safety thresholds. This combined approach was used to inform future dose-strength selection and treated BSA limits. Results Data from 256 patients were analyzed. Patient type, dose strength, and frequency had significant impacts on the dose–exposure relationship. Systemic concentration in patients with PsO was predicted to be 45% lower than in patients with AD from the same dose. When topically applied to the same percentage BSA, brepocitinib systemic exposures are expected to be comparable between adults and children. The systemic steady-state exposure after 3% once daily and twice daily (2 mg/cm 2 ) cream applied to less than 50% BSA in patients with AD and PsO, respectively, maintains at least a threefold margin to non-clinical safety findings and clinical hematologic markers. Conclusion The relationship between the amount of active drug applied and brepocitinib systemic C Trough , described by LMER, may inform the development strategy for dose optimization in the brepocitinib topical program.

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Associations between total mercury, trace minerals, and blood health markers in Northwest Atlantic white sharks (Carcharodon carcharias) - Lisa M. Crawford; James Gelsleichter; Alisa L. Newton; Lisa A. Hoopes; Cheng-Shiuan Lee; Nicholas S. Fisher; Douglas H. Adams; Maeva Giraudo; Anne E. McElroy (Marine Pollution Bulletin, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

Experimental investigation of the cooling capacity and thermal performance of the passive displacement dual cooling coil system in tropical climate - Steve Kardinal Jusuf; Aung Myat; Hui An; Yong Loke Soh; Jeggathishwaran Panisilvam; Peng Cheng Wang; Jing Hui Soo; Nicholas Tan; Poh Hong Neo; George Ng (Building and Environment, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

Open habitats increase vulnerability of amphibian tadpoles to climate warming across latitude - Chung‐Te Cheng; Ming‐Feng Chuang; Takashi Haramura; Chaun‐Bin Cheng; Ye Inn Kim; Amaël Borzée; Chi‐Shiun Wu; Yi‐Huey Chen; Yikweon Jang; Nicholas C. Wu; Yeong‐Choy Kam (Global Ecology and Biogeography, 2023)
Aim Global warming and deforestation are pushing species closer to their physiological limit, especially for species with habitat‐restricted life stages because sunlit areas have higher maximum temperatures. Here, we examined the critical thermal maximum (CT max ), and maximum environmental water temperature (T max ) of larvae from 29 anuran species across a latitudinal gradient (22–43° N) to test how latitude and habitat type (open or closed‐forest ponds) affected warming tolerance, an index of vulnerability to climate change. Location Taiwan, Korea, Japan. Time period Present. Major taxa studied Anurans. Results We showed that open ponds lowered warming tolerance, regardless of latitude and phylogenetic clustering, contrasting the established literature that warming tolerance is lower at tropical latitudes, which only applied to species in forest ponds in this study. Importantly, biophysical models at the local scale suggest that increasing deforestation will exacerbate the effects of climate warming on warming tolerance. Main conclusions Local effects of accelerated warming and habitat modification mean that species with range‐restricted life stages will become more vulnerable to anthropogenic change.

Maize/soybean intercropping improves stability of soil aggregates driven by arbuscular mycorrhizal fungi in a black soil of northeast China - Shu Zhang; Lingbo Meng; Jian Hou; Xiaodan Liu; Abiola O. Ogundeji; Zeyu Cheng; Tengjiao Yin; Nicholas Clarke; Baozhong Hu; Shumin Li (Plant and Soil, 2022)

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

Effects of three feeding modes on the metabolism, antioxidant capacity, and metabolome of the adult male Chinese mitten crab Eriocheir sinensis - Xiaowen Long; Jie Pan; Nicholas M. Wade; Yunfei Sun; Yuming Liu; Yongxu Cheng; Xugan Wu (Aquaculture International, 2022)

Two heads are better than one: current landscape of integrating QSP and machine learning - Tongli Zhang; Ioannis P. Androulakis; Peter Bonate; Limei Cheng; Tomáš Helikar; Jaimit Parikh; Christopher Rackauckas; Kalyanasundaram Subramanian; Carolyn R. Cho; Ioannis P. Androulakis; Peter Bonate; Ivan Borisov; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2022)
Quantitative systems pharmacology (QSP) modeling is applied to address essential questions in drug development, such as the mechanism of action of a therapeutic agent and the progression of disease. Meanwhile, machine learning (ML) approaches also contribute to answering these questions via the analysis of multi-layer ‘omics’ data such as gene expression, proteomics, metabolomics, and high-throughput imaging. Furthermore, ML approaches can also be applied to aspects of QSP modeling. Both approaches are powerful tools and there is considerable interest in integrating QSP modeling and ML. So far, a few successful implementations have been carried out from which we have learned about how each approach can overcome unique limitations of the other. The QSP + ML working group of the International Society of Pharmacometrics QSP Special Interest Group was convened in September, 2019 to identify and begin realizing new opportunities in QSP and ML integration. The working group, which comprises 21 members representing 18 academic and industry organizations, has identified four categories of current research activity which will be described herein together with case studies of applications to drug development decision making. The working group also concluded that the integration of QSP and ML is still in its early stages of moving from evaluating available technical tools to building case studies. This paper reports on this fast-moving field and serves as a foundation for future codification of best practices.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Asian Cities are Greening While Some North American Cities are Browning: Long-Term Greenspace Patterns in 16 Cities of the Pan-Pacific Region - Jiali Jin; Sarah E. Gergel; Yuhao Lu; Nicholas C. Coops; Cheng Wang (Ecosystems, 2020)

Spatial and temporal variations of PM2.5 mass closure and inorganic PM2.5 in the Southeastern U.S. - Bin Cheng; Lingjuan Wang-Li; Nicholas Meskhidze; John Classen; Peter Bloomfield (Environmental Science and Pollution Research, 2019)

Microbial generation of elemental mercury from dissolved methylmercury in seawater - Cheng‐Shiuan Lee; Nicholas S. Fisher (Limnology and Oceanography, 2019)
Elemental mercury (Hg 0 ) formation from other mercury species in seawater results from photoreduction and microbial activity, leading to possible evasion from seawater to overlying air. Microbial conversion of monomethylmercury (MeHg) to Hg 0 in seawater remains unquantified. A rapid radioassay method was developed using gamma‐emitting 203 Hg as a tracer to evaluate Hg 0 production from Hg(II) and MeHg in the low pM range. Bacterioplankton assemblages in Atlantic surface seawater and Long Island Sound water were found to rapidly produce Hg 0 , with production rate constants being directly related to bacterial biomass and independent of dissolved Hg(II) and MeHg concentrations. About 32% of Hg(II) and 19% of MeHg were converted to Hg 0 in 4 d in Atlantic surface seawater containing low‐bacterial biomass, and in Long Island Sound water with higher bacterial biomass, 54% of Hg(II) and 8% of MeHg were transformed to Hg 0 . Decreasing temperatures from 24°C to 4°C reduced Hg 0 production rates cell −1 from Hg(II) 3.3 times as much as from a MeHg source. Because Hg 0 production rates were linearly related to microbial biomass and temperature, and microbial mercuric reductase was detected in our field samples, we inferred that microbial metabolic activities and enzymatic reactions primarily govern Hg 0 formation in subsurface waters where light penetration is diminished.

The association between smoking cessation before and after diagnosis and non-muscle-invasive bladder cancer recurrence: a prospective cohort study - Frits H. M. van Osch; Sylvia H. J. Jochems; Raoul C. Reulen; Sarah J. Pirrie; Duncan Nekeman; Anke Wesselius; Nicholas D. James; D. Michael A. Wallace; K. K. Cheng; Frederik J. van Schooten; Richard T. Bryan; Maurice P. Zeegers (Cancer Causes & Control, 2018)

Fruit and vegetable intake and the risk of recurrence in patients with non-muscle invasive bladder cancer: a prospective cohort study - Sylvia H. J. Jochems; Frits H. M. van Osch; Raoul C. Reulen; Mitch van Hensbergen; Duncan Nekeman; Sarah Pirrie; Anke Wesselius; Frederik-Jan van Schooten; Nicholas D. James; D. Michael A. Wallace; Richard T. Bryan; K. K. Cheng; et al. (Cancer Causes & Control, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Using DNA barcoding to track seafood mislabeling in Los Angeles restaurants - Demian A. Willette; Sara E. Simmonds; Samantha H. Cheng; Sofia Esteves; Tonya L. Kane; Hayley Nuetzel; Nicholas Pilaud; Rita Rachmawati; Paul H. Barber (Conservation Biology, 2017)
Seafood mislabeling is common in both domestic and international markets. Studies on seafood fraud often report high rates of mislabeling (e.g., >70%), but these studies have been limited to a single sampling year, which means it is difficult to assess the impact of stricter governmental truth‐in‐labeling regulations. We used DNA barcoding to assess seafood labeling in 26 sushi restaurants in Los Angeles over 4 years. Seafood from 3 high‐end grocery stores were also sampled ( n = 16) in 2014. We ordered 9 common sushi fish from menus, preserved tissue samples in 95% ethanol, extracted the genomic DNA, amplified and sequenced a portion of the mtDNA COI gene, and identified the resulting sequence to known fish sequences from the National Center for Biotechnology Information nucleotide database. We compared DNA results with the U.S. Food and Drug Administration (FDA) list of acceptable market names and retail names. We considered sushi‐sample labels that were inconsistent with FDA names mislabeled. Sushi restaurants had a consistently high percentage of mislabeling (47%; 151 of 323) from 2012 to 2015, yet mislabeling was not homogenous across species. Halibut, red snapper, yellowfin tuna, and yellowtail had consistently high ( 15%). All sampled sushi restaurants had at least one case of mislabeling. Mislabeling of sushi‐grade fish from high‐end grocery stores was also identified in red snapper, yellowfin tuna, and yellowtail, but at a slightly lower frequency (42%) than sushi restaurants. Despite increased regulatory measures and media attention, we found seafood mislabeling continues to be prevalent.

Methylmercury uptake by diverse marine phytoplankton - Cheng‐Shiuan Lee; Nicholas S. Fisher (Limnology and Oceanography, 2017)

Parallel linear dynamic models can mimic the McGurk effect in clinical populations - Nicholas Altieri; Cheng-Ta Yang (Journal of Computational Neuroscience, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Fruit skin color and the role of anthocyanin - Emrul Kayesh; Lingfei Shangguan; Nicholas Kibet Korir; Xin Sun; Nadira Bilkish; Yanping Zhang; Jian Han; Changnian Song; Zong-Ming Cheng; Jinggui Fang (Acta Physiologiae Plantarum, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Preliminary assessment for global warming potential of leading contributory gases from a 40-in. LCD flat-screen television - Nicholas J. Thomas; Ni-Bin Chang; Cheng Qi (The International Journal of Life Cycle Assessment, 2012)

Reconciling stochastic origin firing with defined replication timing - Nicholas Rhind; Scott Cheng-Hsin Yang; John Bechhoefer (Chromosome Research, 2010)

Effects of substrate availability on the temperature sensitivity of soil organic matter decomposition - ALEXANDER GERSHENSON; NICHOLAS E. BADER; WEIXIN CHENG (Global Change Biology, 2009)
Soil carbon is a major component in the global carbon cycle. Understanding the relationship between environmental changes and rates of soil respiration is critical for projecting changes in soil carbon fluxes in a changing climate. Although significant attention has been focused on the temperature sensitivity of soil organic matter decomposition, the factors that affect this temperature sensitivity are still debated. In this study, we examined the effects of substrate availability on the temperature sensitivity of soil respiration in several different kinds of soils. We found that increased substrate availability had a significant positive effect on temperature sensitivity, as measured by soil Q 10 values, and that this effect was inversely proportional to original substrate availability. This observation can be explained if decomposition follows Michaelis–Menten kinetics. The simple Q 10 model was most appropriate in soils with high substrate availability.

Surprisingly minor influence of TRAV11 (Vα14) polymorphism on NK T-receptor mCD1/α-galactosylceramide binding kinetics - Bee-Cheng Sim; Kaisa Holmberg; Stephane Sidobre; Olga Naidenko; Nathalie Niederberger; Shane D. Marine; Mitchell Kronenberg; Nicholas R. J. Gascoigne (Immunogenetics, 2003)